2015
DOI: 10.1007/s00432-015-1980-8
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of HOTAIR for predicting clinical outcome in patients with digestive system tumors

Abstract: The results suggest that aberrant HOTAIR expression may serve as a candidate positive marker to predict the prognosis of patients with carcinoma of digestive system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…LncRNAs participate in the diverse biological process, and abnormal expression of lncRNAs is associated with human cancers [36, 37]. Cumulative studies have suggested that lncRNAs polymorhisms have been widely studied, and are associated with cancer risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LncRNAs participate in the diverse biological process, and abnormal expression of lncRNAs is associated with human cancers [36, 37]. Cumulative studies have suggested that lncRNAs polymorhisms have been widely studied, and are associated with cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the identification of large number of lncRNAs, aberrant expression of lncRNAs have been widely studied, and several meta-analysis have been done to evaluate the expression of lncRNAs and the prognosis of cancer [36, 43]. At present, there have no study to systematically investigate the association between lncRNAs polymorphisms and cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…Investigators have previously used this program to extract data for behavior-analytic publications (Bowman-Perrot, Burke, Zaini, Zhang, & Vannest, 2015) and in other fields such as oncology (Ma et al, 2015; Zhou et al, 2015) and bio-technology (Prieto, Vázquez, & Murado, 2014). …”
Section: Methodsmentioning
confidence: 99%
“…For examples, high HOTAIR level is correlated to poor prognosis in digestive system tumors [38], estrogen-dependent malignant tumors [39], breast cancer, non-small cell lung cancer, laryngeal carcinoma [40], diffuse large B cell lymphoma [41], bladder transitional cell carcinoma [42] and acute leukemia [43]. Thus, HOTAIR is a key LncRNA in genesis and development of cancer.…”
Section: Discussionmentioning
confidence: 99%